2010
DOI: 10.4103/0974-8520.77162
|View full text |Cite
|
Sign up to set email alerts
|

Antipyretic activity of Guduchi Ghrita formulations in albino rats

Abstract: The present pharmacological investigation was undertaken to study the anti-pyretic activity of Guduchi ghrita formulations in albino rats against yeast induced pyrexia. Seven groups of six animals were used for the experiment. The yeast induced pyrexia method was standardized first by injecting 12.5% yeast suspension (s.c) followed by recording the rectal temperature at regular intervals. Then the evaluation of anti-pyretic activity of Guduchi ghrita formulations was carried out by using this standard procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The results revealed that the body temperature was elevated 18 h after the injection of this pyrogenic agent which continues to elevate up to the 4th h after initiation of fever in the positive control group. These results were in accordance with other research …”
Section: Discussionsupporting
confidence: 94%
“…The results revealed that the body temperature was elevated 18 h after the injection of this pyrogenic agent which continues to elevate up to the 4th h after initiation of fever in the positive control group. These results were in accordance with other research …”
Section: Discussionsupporting
confidence: 94%
“…Fever, inflammation, and pain are traditionally treated with T. cordifolia preparations ( Ashok et al., 2011 , Hussain et al., 2015 ). These preparations can reduce carrageenan-induced edema, indicating their anti-inflammatory potential ( Biswajyoti et al., 2014 ).…”
Section: Promising Pharmacological Activities Of Guduchi ( mentioning
confidence: 99%
“…According to the classical view, the genesis of fever is precipitated by means of inflammatory mediators (i.e., cytokines, namely interleukin-1, interleukin-6, tumor necrosis factor, and others) that are predominantly released by activated peripheral mononuclear phagocytes and different immune cells [36,37]. Due to the fact that direct get admission to of the large hydrophilic cytokine proteins to the temperature-controlling brain buildings within the pre-optic/anterior hypothalamic areas is prevented by means of the blood-brain barrier, the mechanisms described under have been cautioned for producing pyrexia [38]. The ethanolic extract of the flora of M. concanensis also showed antipyretic activity.…”
Section: Antipyretic Activitiesmentioning
confidence: 99%